Permanent structural anisotropy in a hybrid fiber optical waveguide - Yang, Xu; Scannell, Garth; Jain, Chhavi; Rodrigues, Bruno Poletto; Schmidt, Markus A.; Wondraczek, Lothar (Applied Physics Letters, 2017)
The shearing of a liquid with a one-dimensional molecular structure causes structural anisotropy through chain orientation. Here, we exploit this behavior to generate a hybrid fiber optical waveguide with tailored transversal anisotropy. Preferentially oriented chains of silver metaphosphate glass are obtained by pressure-assisted melt filling of silica micro-capillaries at several filling temperatures, pressures, internal capillary diameters, and filling times. Accurate control of the aforementioned parameters enables the adjustment of the degree of anisotropy within limits. Annealing of the waveguides induces volume shrinkage, which is taken as further evidence for the alignment of phosphate chains. These are the first steps towards a novel paradigm for producing glass-based fiber waveguides in which the transversal anisotropy is used to alter optical functionality.
CRIS-Team Scopus Importer:2023-04-20